2021
DOI: 10.1111/peps.12445
|View full text |Cite
|
Sign up to set email alerts
|

With a frown or a smile: How leader affective states spark the leader‐follower reciprocal exchange process

Abstract: Despite evidence that affect shapes perceptions of workplace relationships, the role of affect in the reciprocal exchange process of leader-member exchange (LMX) theory is often overlooked. We argue that this is likely due to a continued focus on global assessments of LMX quality, rather than examination of the reciprocal, interlocked actions and reactions that take place daily between members of the dyad. A leader's affective state may indeed spark this reciprocal exchange process on a daily level and ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 163 publications
(215 reference statements)
2
15
0
Order By: Relevance
“…We found that the existence of leaders does not always improve the level of individual cooperation. This conclusion is consistent with the previous research conclusion of leader style (Tong, 2020;Zeng et al, 2020;Bartels et al, 2022). By controlling the investment of leaders, we found that only when the leader's investment is close to all his capital the employees will improve the level of cooperation and increase the investment.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that the existence of leaders does not always improve the level of individual cooperation. This conclusion is consistent with the previous research conclusion of leader style (Tong, 2020;Zeng et al, 2020;Bartels et al, 2022). By controlling the investment of leaders, we found that only when the leader's investment is close to all his capital the employees will improve the level of cooperation and increase the investment.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…This setting is consistent with settings (Tong, 2020) and (Bartels et al, 2022) except for the investment of leaders. We set the leader's investment in the group project to be randomly selected from 42 to 45G$ to reflect the power of the leader's role model.…”
Section: Experimental Setup Under High Investment Type Leaderssupporting
confidence: 71%
See 3 more Smart Citations